Educating the whole child : cross-curricular skills, themes, and dimensions (Open University Press, 1995)
Cross-curricular skills, themes and dimensions: an introduction. Little citizens: helping children to help each other. Effective schooling for all: the 'special educational needs' dimension. Racial equality education: identity, curriculum and pedagogy...